AVALIAÇÃO DE UM PROGRAMA DE RASTREAMENTO MÓVEL DO CÂNCER DO COLO DO ÚTERO EM SÃO LUÍS, MA: IMPACTO E DESAFIOS PARA O RASTREAMENTO EFICIENTE. - LEAL, Rachel Jorge Dino Cossetti (2019)
Cervical cancer (CC) is the most frequent cause of cancer and cancer-related mortality in women in Maranhão. The Brazilian national screening program recommends cervical cytology (Pap test) every three years in women 25 to 64 years of age who have initiated sexual activity. This was a prospective, intervention-based, analytic study to evaluate a CC screening program through a mobile screening unit (MSU), in several communities in São Luís, from April to August/2018. Women were invited for CC screening. Screening test were carried out and their results were returned on the scheduled date, along with information about the need for complementary tests. Quality control and monitoring was carried out. A structured questionaire was applied. 960 appointments were carried out in 15 communities, and 545 women aswered the questionare. Median age was 43 years (34 – 52), with 88,2% of women in the recommended target age. Socioeconomic charachteristics: 47,3% completed high school education, 37,8% were housewives, 16,1% were unemployed, 56,3% were married/in a stable union, and 59,8% had a monthly familiy income of up to 1 minimum wage. About undergoing Pap test and related difficulties: 94,1% underwent at least one previous test, 78,2% had a test within the past three years, 48,4% referred to dificculties to schedule the test, 23,3% time constraints, 11,2% being ashamed shame, and 10,4% financial restrains. The mobile screening unit (MSU) strategy enabled overcoming the geographic barrier to screening through facilitated access to a test with quality control within the national guidelines recommendations and retrieval of results within a reasonable timeframe accompanied by trained health professional guidance. The most importante barriers to efficient screening were the non-organized process of invitation of the target population, unavailability of the MSU to perform tests on an alternative date and the follow-up tests following the screening guidelines recommended intervals, failure to follow-up positive cases, with difficulty to assure reference to secondary units capable of performing additional investigation. Incorporation of low-cost technology for more rigorous follow-up of screening flow, results and propaedeutics could improved management and effectiveness of CC screening.